Medicinal Trees of Uttaranchal State: Distribution , Use Pattern and Prospects for Conservation - Adhlkari, B. S.; Babu, M. M.; Saklani, P. L.; Rawat, G. S. (Indian Forester, 2003)
This paper deals with distribution and use pattern of medicinal trees in the State of Uttaranchal , India. Based on extensive literature survey , a list of 197 medicinal trees found in Uttaranchal has been appended. Their altitudinal distribution and parts used in various ailments have been given. Euphorbiaceae , Fabaceae , Moraceae and Rosaceae are the largest families having more than 10 species of medicinal trees. The medicinal trees in different ecological regions found in sub-tropical , warm temperate , cool-temperate , sub-alpine and alpine are 170 , 64 ,22 ,10 and 4 , respectively. The major parts used in various ailments are bark (118 species) , leaves (78 species) , fruits (65 species) , root (42 species) and seed (30 species). The diseases such as dysentery , fever , diarrhoea , rheumatism , wounds , cholera , skin diseases , bronchitis , cough and asthma are the most frequent ailments. The prospects of in-situ and ex-situ conservation of medicinal trees in Uttaranchal State have been discussed.